2008
DOI: 10.1007/s10456-008-9127-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and RANKL differentially regulate angiogenesis and endothelial cell function

Abstract: Osteoprotegerin (OPG) a soluble tumor necrosis factor receptor family molecule protects endothelial cells from apoptosis in vitro and promotes neovascularization in vivo. In this study, we assessed the role of OPG and its ligands, receptor activator of nuclear factor-kappaB ligand (RANKL) and tumor necrosis factor-related apoptosis inducing ligand (TRAIL), in microvessel formation using the rat aortic ring model of angiogenesis. OPG was found to promote a twofold increase in angiogenic sprouting in the aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 49 publications
2
61
0
1
Order By: Relevance
“…[32][33][34] Further, OPG can stimulate angiogenesis or endothelial cell survival in cell culture or aortic ring explants. 35,36 In agreement with these findings, when equivalent concentrations of OPG to those used to inhibit metatarsal angiogenesis were tested in the HUVEC/fibroblast coculture angiogenesis assay, which lacks osteoclasts, we observed a slight stimulation rather than any inhibition of angiogenesis in the HUVEC cultures (data not shown). It is unclear whether PTHrP can directly inhibit or stimulate endothelial cells.…”
Section: Discussionsupporting
confidence: 68%
“…[32][33][34] Further, OPG can stimulate angiogenesis or endothelial cell survival in cell culture or aortic ring explants. 35,36 In agreement with these findings, when equivalent concentrations of OPG to those used to inhibit metatarsal angiogenesis were tested in the HUVEC/fibroblast coculture angiogenesis assay, which lacks osteoclasts, we observed a slight stimulation rather than any inhibition of angiogenesis in the HUVEC cultures (data not shown). It is unclear whether PTHrP can directly inhibit or stimulate endothelial cells.…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned above, OPG exerts an antiapoptotic effect towards TRAIL and decreases in consequence the number of apoptotic bodies that may serve as nucleation sites for passive mineralization (Fleishman et al 1990;Benslimane-Ahmim et al 2011). Several studies have shown also that recombinant OPG can promote the survival/proliferation of mature vascular endothelial cells (Malyankar et al 2000;Pritzker et al 2004;Cross et al 2006;Kobayashi-Sakamoto et al 2006;McGonigle et al 2009). Similarly, Lawrie et al showed OPG promotes the proliferation and the migration of pulmonary artery smooth muscle cell, and thus evidenced an important role of OPG in the pathogenesis of pulmonary arterial hypertension (Lawrie et al 2008).…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 99%
“…Previous data reported an inhibitory role of RANKL in angiogenesis (14,15), which could explain its lower serum levels in patients compared to controls. To evaluate angiogenesis, we administered serum VEGF, which is a key angiogenic factor mediating neo-vascularization and could act as a surrogate marker of tumor angiogenesis (40).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the known role of RANKL in the skeletal and immune systems (13), recent studies also reported a role of RANKL in angiogenesis. Certain authors support an inhibitory role of RANKL (14,15), whereas others showed a stimulating action on angiogenesis (16). Contrary to RANKL, VEGF is known as a potent mitogen angiogenic factor and is one of the most important molecules involved in the vascularization of bone tissue (17), thus its serum levels are considered an index of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%